1923 N.D. Laws 381 - (:unkn) unknown (My University, 1923)
Ch. 266, § 10: No person shall sell, deliver, or otherwise transfer a pistol or revolver to a person who he has reasonable cause to believe either is an unnaturalized foreign born person or has been convicted of a felony against the person or property of another, or against the Government of the United States or any State or subdivision thereof, nor in any event shall he deliver a pistol or revolver on the day of the application for the purchase thereof, and when delivered, said pistol or revolver shall be securely wrapped and shall be unloaded. Also provided licensure requirements for dealers.
Keywords: LICENSE - DEALERS; TRANSFER - DANGEROUS PERSONS